Amino Acid Intakes Are Associated With Bone Mineral Density and Prevalence of Low Bone Mass in Women: Evidence From Discordant Monozygotic Twins. (30th September 2015) - Jennings, Amy; MacGregor, Alexander; Spector, Tim; Cassidy, Aedín
ABSTRACT: Although a higher protein intake, particularly from vegetable sources, has been shown to be associated with higher bone mineral density (BMD) the relative impact of specific amino acids on BMD and risk of osteoporosis remains to be determined. Mechanistic research suggests that a number of specific amino acids, including five nonessential amino acids—alanine, arginine, glutamic acid, glycine, and proline—may play a role in bone health, principally through improved production of insulin and insulin‐like growth factor 1 and the synthesis of collagen and muscle protein. However to date, no previous studies have examined the associations between habitual intake of amino acids and direct measures of BMD and prevalence of osteoporosis or osteopenia, and no studies have examined this relationship in discordant identical twin‐pairs. In these analyses of female monozygotic twin‐pairs discordant for amino acid intake ( n = 135), twins with higher intakes of alanine and glycine had significantly higher BMD at the spine than their co‐twins with within‐pair differences in spine‐BMD of 0.012 g/cm 2 (SE 0.01; p = 0.039) and 0.014 g/cm 2 (SE 0.01; p = 0.026), respectively. Furthermore, in cross‐sectional multivariable analyses of 3160 females aged 18 to 79 years, a higher intake of total protein was significantly associated with higher DXA‐measured BMD at the spine (quartile Q4 to quartile Q1: 0.017 g/cm 2, SE 0.01, p = 0.035) and forearm (Q4 to Q1: 0.010 g/cm 2, SE 0.003, p = 0.002). Intake of six amino acids (alanine, arginine, glutamic acid, leucine, lysine, and proline) were associated with higher BMD at the spine and forearm with the strongest association observed for leucine (Q4 to Q1: 0.024 g/cm 2, SE 0.01, p = 0.007). When intakes were stratified by protein source, vegetable or animal, prevalence of osteoporosis or osteopenia was 13% to 19% lower comparing extreme quartiles of vegetable intake for five amino acids (not glutamic acid or proline). These data provide evidence to suggest that intake of protein and several amino acids, including alanine and glycine, may be beneficial for bone health, independent of genetic background. © 2015 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.